Evaluating the English Textbook "English for Iraq" for the 2nd Intermediate Stage (Journal of the College of Basic Education, 2022)
The current research aims to evaluate the content of the English language book for the second intermediate grade in Iraqi schools. The evaluation includes the internal and some external aspects of the book for several reasons, including that the content of the book is not commensurate with the specified time period, and the level of achievement of the learner of English as a foreign language in Iraq. It has not long been satisfactory to those who work in education. The researcher believes that one of the main factors that contributed to the students' unsatisfactory achievement can be attributed to the textbook. Therefore, textbooks for English as a foreign language must be evaluated and improved periodically, as the evaluation of textbooks is a stage that precedes their adoption or modification, and many educators believe that there is a need to review and update the curricula and their contents, and the researcher believes that looking at books in English is similar to looking at devices, where The computer should be updated periodically and keep up with new technologies that add excitement and learning for learners. Evaluation will simplify textbook approval and modification.The researcher used the analytical descriptive approach in her research, which included a list of the various internal and external aspects of the textbook for the second intermediate stage students in Iraq. These paragraphs (45) were divided into six main axes:A- Achieving the general goals of English as a foreign language in the intermediate stage and the learners' needs.B- Academic content.C- Vocabulary and grammar.d- Exercises and activitiesH- Attractive text and guidance.h- Accompanying means.Weaknesses in the book1. It does not achieve the national goals for education.2. The presence of the local environment is not noticeable3. The book's ideas lack logic and organization.4. The font size is smaller than usual.5. The content is almost incompatible with the student's culture and does not use much knowledge on the subject.6. There is no balance between controlled and free textbook exercises, and these exercises lack gradation.